2022
DOI: 10.1007/s00127-022-02315-w
|View full text |Cite
|
Sign up to set email alerts
|

Adverse childhood experiences and cognitive function in adulthood: examining the roles of depressive symptoms and inflammation in a prospective cohort study

Abstract: Purpose Adverse childhood experiences (ACEs) have been associated with cognitive decline in adulthood. However, the underlying mechanisms implicated remain unclear. This study investigated depressive symptoms and systemic inflammation as potential mediators of the association between ACEs and later cognitive function. Methods Participants were adults aged 50 + from the English Longitudinal Study of Ageing (N = 3029; 54.8% female). Measures included self-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 83 publications
0
8
0
Order By: Relevance
“…Depression was found to mediate the relationship between ACHEs and cognitive functioning, which is consistent with findings relating to ACEs. Evidence suggests that depressive symptoms may be indirectly responsible for cognitive decline following ACEs [ 48 , 92 ]. It indicates that adverse childhood health experiences might lead to depression which can increase the risk of cognitive impairment in the middle-aged and elderly population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Depression was found to mediate the relationship between ACHEs and cognitive functioning, which is consistent with findings relating to ACEs. Evidence suggests that depressive symptoms may be indirectly responsible for cognitive decline following ACEs [ 48 , 92 ]. It indicates that adverse childhood health experiences might lead to depression which can increase the risk of cognitive impairment in the middle-aged and elderly population.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has been found that depression has been implicated as one of the risk factors for dementia, recent years have seen significant attention paid to depression because of its association with cognition [ 44 ], and significant correlations have been demonstrated in recent studies to suggest that depression is closely related to cognition [ 45 47 ]. Also, it is generally observed that depression plays a mediating role in studies of cognitive abilities [ 48 51 ]. Therefore, the purpose of this study was to investigate whether ACHEs have an impact on cognitive function in Chinese middle-aged and older adults through depression levels as a mediating variable.…”
Section: Introductionmentioning
confidence: 99%
“…Patients will be cognitively assessed by n -back working memory paradigm and NIH Toolbox Cognitive Battery to determine whether COVID-19 contributes to decreased fluid and/or crystalized cognitive performance. Patients will also complete select questionnaires from Emotion Battery (Emotional Support, Friendship, Loneliness, Perceived Hostility, Perceived Rejection, and Instrumental Support questionnaires) and Adverse Childhood Experience questionnaire to determine current state of social support/interaction and traumatic events during childhood, both of which are known to exacerbate and contribute to cognitive impairment [ 44 , 45 ]. All cognitive, emotional, and adverse childhood experience assessments will be performed at baseline and 18-month follow-up.…”
Section: Study Aims and Protocolmentioning
confidence: 99%
“…[14][15][16] A prospective cohort study discovered cognitive impairments and ACEs that were mediated in part by depressive symptoms. 5 Additionally, empirical support suggests that daily hassles and negative life events (NLEs) are correlated with symptoms of depression, negative affect, and neuroticism. NLEs and daily difficulties encompass disagreeable and anxiety-inducing obligations such as familial disputes, financial hardships, and work-related obligations.…”
Section: Introductionmentioning
confidence: 99%
“…1416 A prospective cohort study discovered cognitive impairments and ACEs that were mediated in part by depressive symptoms. 5…”
Section: Introductionmentioning
confidence: 99%